Diplopylidium polyacantha sp. n. (Cestoda, Dipylidiidae) — новая цестода плотоядных - Великанов, В.П. (Вестник зоологии, 1982)
Adult stage of a cestode reared under experimantal inoculation of carnivores (cat, fox, dog) with cysticercoids obtained from reptiles is described as a new species, Diplo pylidium polyacantha sp. n. It is distinct fromother Diplopylidium species by the presence of 8-11 transverse hook rows, their shape and other characters.